2017
DOI: 10.1111/bpa.12546
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray methodology identifies complement pathway activation and dysregulation in progressive multiple sclerosis

Abstract: The complement pathway has potential contributions to both white (WM) and grey matter (GM) pathology in Multiple Sclerosis (MS). A quantitative assessment of complement involvement is lacking. Here we describe the use of Tissue MicroArray (TMA) methodology in conjunction with immunohistochemistry to investigate the localization of complement pathway proteins in progressive MS cortical GM and subcortical WM. Antibodies targeting complement proteins C1q, C3b, regulatory proteins C1 inhibitor (C1INH, complement r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
5
29
0
Order By: Relevance
“…This work confirms that complement activation and dysregulation occur in all cases of MS [11]. In addition, the authors of recent study reported that C3d microglial clusters are present in chronic but not acute MS lesions.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This work confirms that complement activation and dysregulation occur in all cases of MS [11]. In addition, the authors of recent study reported that C3d microglial clusters are present in chronic but not acute MS lesions.…”
Section: Introductionsupporting
confidence: 87%
“…We have previously shown that astrocytes in culture can secrete most of the complement proteins and expression is markedly enhanced by TNFĪ±, IL-1Ī² and IL-8 [10]. In addition C5b-9 deposits were found in macrophages [5], neurons [11] and OLG progenitor cells [12]. …”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that complement is activated in progressive MS GM neurons and complement activation correlated with severity of GM pathology, whereas others have shown that complement C1q and C3b expression is associated with degenerating synapses in the progressive MS hippocampus . We performed ISH for complement transcripts that encode the recognition fragment C1q and the central complement component C3.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the differentially expressed genes and related biological processes found in each OPC cluster complement emerging literature that indicates non-canonical roles for OPCs during homeostasis, and a more active role of this cell type in multiple diseases. For example, OPC1 expresses high levels of Clusterin, a gene known to be upregulated in both Alzheimer's disease and multiple sclerosis (MS) 61,62 . OPCs have recently been shown to potentially play an active role in the pathology of MS and have been implicated in the progression of Alzheimer's disease 17,20,63 .…”
Section: Discussionmentioning
confidence: 99%